Unravelling The Auditors’ Dilemma: Ethics Or Money? A Case Of Indonesia Auditors - Hikmah Islamiati; Nuraini A; Nita Erika Ariani (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine several influencing factors of auditors’ behavior in ethical dilemma situations and whether auditor behavior in ethical dilemmas is driven by the love of money Methodology/Approach: This study populations are all external auditors in Indonesia period 2019 with 282 auditors as samples. Partial Least Squares analysis (PLS) was used to analyze the data obtained. Findings: This study reveals that in an ethical dilemma situation, experience and level of education do not affect auditor behavior. However, idealism and love of money affect auditor behavior. While an auditor's experience increases the love of money, the more experienced an auditor is, the lower the level of love of money is. In dilemma situations, the love of money mediates the effect of education and experience on ethical behavior. Excessive love for money can arise through the process of socialization that is obtained and maintained in life. Practical implications: These findings prove that love of money mediate the relationship between the influencing factor of auditor’s behavior Originality/value: The novelty of this study lies in love of money as intervening variable on the relationship between the influencing factor of auditor’s behavior in ethical dilemma situations which has never been done in previous research.